Structural aspects in tonsillitis vs normal - Chesca, A.; Sandle, T.; Abdulina, G.A.; Anamaria, P. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The pathology of childhood occurring with increased frequency is tonsillitis. The infection affects both sexes equally, without any association with environmental factors. The symptomatology attracts attention and requires treatment by a specialized medical team. The severity of the symptoms often leads to surgery to remove these formations via a tonsillectomy. An important step in management for tonsillitis understands the microbiological and pathological aspects. After performing microscopic slides, the preparations are examined by performing microscopic analysis. The process of the permanent microscopic preparations was based on prior knowledge of the steps from the classical method, using a standard H&E staining technique. Thediagnosis is established by laboratory methods, namely by the analysis of usual or specific-colored permanent microscopic preparations. This paper demonstrates how histological examination can help to differentiate between healthy and infected specimens. The histopathological examination revealed chronic tonsillitis with reactive follicular hyperplasia in all pathological cases of children, useful to mention that timely histopathological investigation of the underlying tissues of the tonsils helps in the accurate indication of microorganisms that are difficult to cultivate. In this context, the histological examination also helps to differentiate colonization from tissue infiltration.
Қалыптыға қарсы тонзиллиттің құрылымдық аспектілері
Структурные аспекты тонзиллита по сравнению с нормой
Keywords: tonsils; pathology; tonsillitis; diagnosis; histopathology; microscopy; follicular hyperplasia